PENGARUH PELAYANAN KOPERASI TERHADAP PARTISIPASI ANGGOTA KUD TIGA KOTO KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Sutriayu Sutriayu; Syakdanur Nas; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This study aims to determine the effect of cooperative services to the participation of members. Research was conducted on KUD Three Koto Districts Koto Kampar Hulu district Kampar with 93 sample obtained using the method of sampling area. The analysis techniques used in this research is Simple mlinear regression analysis. The result showed that the cooperative services affect the participation of members of the cooperative can be seen from the results of a calculated tvalute ( 9.332 ) > Htable ( 1.986 ) or Ho refused and Ha accepted. Furthermore the results of research partially, (R²) of 0.489. What this means is that the percentage effect of cooperative services to the participation of members of 48.9%. While the remaining 51.1% is a variable that is not examined in this study. Keywords : Service Cooperatives, Member Participation